By a Silken Thread : regional banking integration and pathways to financial development in Japan s Great Recession - Mathias Hoffmann; Toshihiro Okubo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Regional differences in banking integration determined how Japan s Great Recession after 1990 spread across the country. We explain these differences with the emergence of silk reeling as the main export industry after Japan s opening to trade in the 19th century. The silk-exporting prefectures developed a system of export finance centered on local, cooperative banks that preserved their dominant local position long after the decline of the silk industry. Our findings suggest that different pathways to financial development can lead to long-term differences in de facto financial integration, even if there are no formal barriers to capital mobility between regions.
Keywords: F15; F30; G01; 330